Construction of high performance CH3NH3PbI3-based solar cells by hot-casting technique - Wang, Shiwei (2017)
Two-dimensional plane CH3NH3PbI3 crystals in millimeter size have been first successfully constructed on FTO glass coated with mesoporous TiO2 by hot-casting technique. Depending on the closely and continuous arrangement of large perovskite crystals in the film, a best power conversion efficiency (PCE) of 16.01% was achieved along with a photocurrent density of 21.32 mA/cm2, an open circuit voltage of 1.07 V and a fill factor of 0.70 from the corresponding CH3NH3PbI3-based solar cells with p-i-n structure. Even more exciting was the quite good stability of the hot-casting-based device, which remained at more than 91% under 55% humidity for 10 days.